Pengaruh Model Project based Learning dan Aktivitas Belajar terhadap Keterampilan Menulis Teks Negosiasi Siswa kelas X di SMAN 1 Pagai Utara Selatan Kabupaten Kepulauan Mentawai - Frida Nur Lestari; Yetty Morelent; Syofiani Syofiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study examines the effect of Project Based Learning (PjBL) on students’ learning activities and negotiation text writing skills at the tenth-grade level of SMAN 1 Pagai Utara Selatan. The research employed a quantitative approach using a quasi-experimental method with a Solomon Four-Group Design. The sample consisted of 80 students divided into two experimental groups and two control groups. Data were collected through a learning activity questionnaire and a writing test, and analyzed using normality testing, homogeneity testing, paired sample t-test, and independent sample t-test at a 0.05 significance level. The results indicate that PjBL significantly improved students’ learning activities (p < 0.001). Within-group analysis showed a significant improvement in writing skills in the experimental group (p < 0.001). However, no statistically significant difference was found between the experimental and control groups in the posttest scores at the 5% level (p = 0.056), although the experimental group achieved a higher mean score. These findings suggest that PjBL effectively enhances learning engagement and contributes to improving negotiation text writing skills.